2010
DOI: 10.1007/s11552-010-9276-6
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Acute Scaphoid Fractures: A Systematic Review and Meta-Analysis

Abstract: Background/Methods The purpose of this review was to assess the current evidence supporting operative fixation versus casting for acute scaphoid fractures through a systematic review and meta-analysis of the literature. Results Our search yielded 59 articles that met our inclusion criteria with five studies achieving high, 22 moderate, and 32 low Structured Effectiveness Quality Evaluation Scale scores. Pooled results of the four Sackett level 1 evidence studies showed no significant difference between the ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 65 publications
(282 reference statements)
0
8
1
Order By: Relevance
“…Previous meta-analysis and systematic reviews have lacked effective research on patient satisfaction. Suh et al [22] and Symes et al [23] only conducted a qualitative systematic evaluation and lacked a quantitative meta-analysis. Although Buijze et al [21] tried to perform quantitative analysis, they only included Bond et al's study.…”
Section: Discussionmentioning
confidence: 99%
“…Previous meta-analysis and systematic reviews have lacked effective research on patient satisfaction. Suh et al [22] and Symes et al [23] only conducted a qualitative systematic evaluation and lacked a quantitative meta-analysis. Although Buijze et al [21] tried to perform quantitative analysis, they only included Bond et al's study.…”
Section: Discussionmentioning
confidence: 99%
“…Eight randomised controlled trials (RCTs) 3,18,[23][24][25][26][27][28] have reported on 463 participants with undisplaced or minimally displaced fractures of the scaphoid waist who had either of these two treatments. These RCTs had small sample sizes (ranging from 25 to 88 participants) and have been systematically reviewed nine times; [29][30][31][32][33][34][35][36][37] these reviews all commented on the low quality of the evidence.…”
Section: Current Evidencementioning
confidence: 99%
“…Nondisplaced acute scaphoid waist fractures can be treated conservatively in a short or long arm cast, or operatively, especially in high-demand patients or those with associated distal radius fractures. 3,70,71 Displaced scaphoid waist fractures and proximal pole fractures, 3 as well as fractures complicated by nonunion or nonunion with osteonecrosis, are usually treated operatively. 42 Transscaphoid perilunate dislocations, and other types of perilunate dislocations associated with scaphoid fractures, such is transscaphoid transcapitate perilunate dislocation, are treated with urgent closed reduction followed by operative treatment.…”
Section: Treatment Of Scaphoid Fractures and Their Complicationsmentioning
confidence: 99%